Processo BIM em projetos de licitações de obras públicas em obras do CRAS-SC - Stradiotto, Júlia (Universidade do Vale do Rio dos Sinos, 2018)
The increase of cost and schedule delays in public construction projects, mostly in developing countries, brings the need to find solutions for this issue. BIM process is understood as an alternative to achieve more transparency in the design and constructions stages. This paper aims to investigate the BIM design process of public constructions of Centro de Referência de Assistência Social (CRAS) of Santa Catarina, which is the first project designed by this State in BIM process. This study aims to analyze reductions of costs overruns and schedule delays, comparing the same project in different bids: the Edital A was designed by traditional process (CAD) and the Edital B was designed in BIM process, analyzing the design and construction stage. This study was developed in three stages: the first investigated the projects made in CAD and construction of Edital A, which includes 61 constructions, but only 46 was built, presenting extremely high schedule delays and costs overruns; the second stage aims to analyze the Edital B, with project reviewed and designed in BIM and 50 constructions; and the third stage refers to the comparison between the first and second stage. In addition, interviews were conducted and two visits to the constructions of the Edital B were required. The results indicate that in the constructions completed of the Edital B, only one construction project was finished according to the cost and schedule originally established, one construction had only schedule delay and another tree were concluded with schedule delays and costs overruns until July 2018. Even though, the constructions of Edital B had cost overruns and schedule delay, the results show gains in relation to Edital A. The design in BIM process with the appropriate quantitative takeoff and the review of the original design were the main responsible for the reduction of the cost overruns. In terms of schedule delays, these were influenced by several factors, the main factor has unknown cause and was observed in both analyses (Edital A and B), besides there are factors related to contracting, construction planning and counterparts of municipalities. The causes related to the design process has shown less relevance in terms of schedule delay.
Keywords: Modelagem da informação da construção; BIM; Obras púbicas; CRAS; Projeto; Building information modeling; BIM; Public projects; CRAS; Project; ACCNPQ::Engenharias::Engenharia Civil